14.4k views
2 votes
Let f(x) = 2x2 − 2x + 7 and g(x) = x2 + 9x − 6. Find f(x) − g(x).

User Davisca
by
6.1k points

1 Answer

0 votes

Answer:

Given information :


f(x) = 2x^2-2x+7\\g(x) = x^2+9x-6

Find f(x) - g(x)


f(x)-g(x) = (2x^2-2x+7) - (x^2+9x-6)

Distribute the negative to the second polynomial


f(x)-g(x)=2x^2-2x+7 -x^2 -9x + 6

optional : rearrange the terms


f(x)-g(x)=2x^2-x^2-2x-9x+7+6

Combine like terms and find f(x) - g(x)


f(x)-g(x) = x^2 - 11x + 13

User Tanner Ottinger
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.